Relationship Between Management Capacity and Job Satisfaction in the Central Body of the Justice Sector of Peru - Martínez Malqui, Shayla Mariel (2025)
This study aimed to determine the correlation between management capacity (MC) and job satisfaction (JS). The research involved a quantitative approach with a non-experimental, cross-sectional design and was conducted on a population of 346 civil servants working in the justice sector of Peru. The MC variable was evaluated based on its four dimensions: planning, organization, management, and control. The JS variable was assessed based on five dimensions: relationship with superiors, interpersonal relations, job challenge, compensation systems, and working conditions. The results showed a robust positive correlation (0.803) between MC and JS. Based on the findings, MC has a positive relationship with JS in all of its dimensions.